Exploring Qibla Accuracy in Coffee Shops: A Study in Padang City - Abdul Hafizh; Afrinal Afrinal (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2024)
Determining the direction of the Qibla is essential before carrying out worship (prayer). This research, through a qualitative study, aims to determine and explore the accuracy of the Qibla direction in coffee shops in Padang City. Observations were carried out at ten coffee shops selected as research samples using several steps: firstly, the crowd of visitors; secondly, the existence of a prayer place in the coffeeshop; and thirdly, the direction or Qibla coordinates of the coffeeshop. The results of this research are as follows: First, coffee shop managers' understanding of the direction of Qibla varies, and more than half of the sample managers are unsure about the direction of Qibla. Second, calibration (recalculation) carried out at ten research locations indicated that the level of accuracy of the Qibla direction was still low. Calculating the Qibla direction at the coffee shop uses the Qibla azimuth (AK) method with coffee shop location coordinates and a GPS application to measure the accuracy of the Qibla direction and compare it with the Mizwala astronomical instrument. Third, Determining the Qibla direction in the coffee shop does not use accurate Qibla direction measurements. Coffee shop managers often rely on building developers or smartphone applications to determine the Qibla direction. Fourth, analysis of Qibla direction calibration in coffee shops shows two main factors: a lack of understanding and awareness of the importance of Qibla direction accuracy by coffee shop managers and the absence of a method for using accurate Qibla direction measurements.